2021
DOI: 10.1007/s11120-021-00879-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of red by green light in the growth spectrum on photomorphogenesis and photosynthesis in tomato plants

Abstract: The artificial light used in growth chambers is usually devoid of green (G) light, which is considered to be less photosynthetically efficient than blue (B) or red (R) light. To verify the role of G light supplementation in the spectrum, we modified the RB spectrum by progressively replacing R light with an equal amount of G light. The tomato plants were cultivated under 100 µmol m–2 s–1 of five different combinations of R (35–75%) and G light (0–40%) in the presence of a fixed proportion of B light (25%) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Such a response, however, was expected, based on the results of previous studies [3,12], and we found that stomatal conductance and NPQ are related to the lighting spectra applied during plant growth in controlled-environment agriculture. It was noticed that the progressive replacement of R light by G light in the growth RB spectrum decreases stomatal dimensions, thus reducing g s and E and, consequently, improving water-use efficiency [12] while decreasing evaporative cooling and presumably increasing foliar temperature [11]. Additionally, the influence of T leaf on g s , which exists independently of the effects exerted through changes in plant water status [13], should be mentioned.…”
Section: Introductionsupporting
confidence: 50%
“…Such a response, however, was expected, based on the results of previous studies [3,12], and we found that stomatal conductance and NPQ are related to the lighting spectra applied during plant growth in controlled-environment agriculture. It was noticed that the progressive replacement of R light by G light in the growth RB spectrum decreases stomatal dimensions, thus reducing g s and E and, consequently, improving water-use efficiency [12] while decreasing evaporative cooling and presumably increasing foliar temperature [11]. Additionally, the influence of T leaf on g s , which exists independently of the effects exerted through changes in plant water status [13], should be mentioned.…”
Section: Introductionsupporting
confidence: 50%
“…Furthermore, Frechilla et al ( 2000 ) also documented that green light was able to reverse the previous blue light-induced stomatal opening response. Previous reports have shown that green light has a regulating effect on stomata (Frechilla et al, 2000 ; Talbott et al, 2002 ), could promote the growth of plants (Kaiser et al, 2019 ; Meng et al, 2020 ; Schenkels et al, 2020 ; Kusuma et al, 2021 ; Trojak et al, 2021 ), partial remediated photosynthetic capacity (Claypool and Lieth, 2021 ), and increased the nutritional quality of plants (Bian et al, 2018a ; Li et al, 2021 ). Moreover, the inclusion of green light in the growth spectrum reduced stomatal conductance (g s ) and transpiration and altered stomatal traits, thus improving water-use efficiency and improving drought tolerance (Bian et al, 2019 ; Trojak et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that green light has a regulating effect on stomata (Frechilla et al, 2000 ; Talbott et al, 2002 ), could promote the growth of plants (Kaiser et al, 2019 ; Meng et al, 2020 ; Schenkels et al, 2020 ; Kusuma et al, 2021 ; Trojak et al, 2021 ), partial remediated photosynthetic capacity (Claypool and Lieth, 2021 ), and increased the nutritional quality of plants (Bian et al, 2018a ; Li et al, 2021 ). Moreover, the inclusion of green light in the growth spectrum reduced stomatal conductance (g s ) and transpiration and altered stomatal traits, thus improving water-use efficiency and improving drought tolerance (Bian et al, 2019 ; Trojak et al, 2021 ). According to Bian et al ( 2019 ), under short-term drought stress, green light significantly decreased g s and increased the intrinsic water-use efficiency (WUE) and instantaneous water-use efficiency (iWUE) of tomato, increased mesophyll conductance, and remained high photosynthetic capacity, which resulted in enhanced drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of light quality on plant development has been largely studied using a growing light environment made up of different combinations of blue and red or white light (Brown et al 1995;Hogewoning et al 2010a;Matsuda et al 2004;Ohashi-Kaneko et al 2006;Yorio et al 2001). Notably, in the just cited studies, the light intensity reported was relatively low, around 200 μmol photons m -2 s -1 , which could underestimate the effect of spectral quality on leaf development and, therefore, on the photosynthetic apparatus (Chen et al 2014;Fang et al 2020;Hamdani et al 2018;Hogewoning et al 2010b;Labeke 2017aLabeke , b, 2018Liu et al 2011;Quero et al 2019;Trojak et al 2022;Trouwborst et al 2016;Vitale et al 2021;Wang et al 2016;Zhang et al 2019;Zheng and Van Yang et al 2017). Furthermore, in all these works, the light intensity remained constant at different spectral qualities.…”
Section: Introductionmentioning
confidence: 99%